Creating Shared Values A Case Study of Bursa Efek Indonesia - Camila Isabel De Sequera Lastrilla (Journal of Sustainable Community Development (JSCD), 2023)
The importance of sustainability has only been highlighted during the COVID-19 pandemic. Companies had widened their perception of success to focus not only on profit, but on people and the planet. The Creating Shared Value approach has evolved from Corporate Philanthropy and Corporate Social Responsibility by utilizing their business model to address real societal needs through the business itself while achieving economic success. Bursa Efek Indonesia or the Indonesia Stock Exchange (IDX) has utilized CSV strategies in their business activities for years. Their organization continually evolving to meet opportunities to include CSV activities in their business plan. Educating the population on smart investing decisions, financial responsibility and good financial management is the main theme of their CSV Strategy. In this chapter, we propose a revolutionary arm to this strategy by attempting to reach a younger market. This strategy aims foster a future talent pool of investors, issuers, regulator and brokers with the ultimate goal of educating the youth to invest in ethical businesses. In the long-term, this CVS strategy will raise a generation of educated and developed minds who want to develop a more efficient, trusted and ethical market.